Problem based learning model using vee diagrams on students' scientific literacy of environmental pollution material - Berti Yolida; Rini Rita T. Marpaung; Revi Handini (JPBIO (Jurnal Pendidikan Biologi), 2021)
One of the factors of the low scientific literacy of students is influenced by the learning model used during the learning process. This study aims to determine the effect of the problem based learning (PBL) model using vee diagrams on environmental pollution material on students' scientific literacy skills. The sample consisted of 68 students, consisting of class VII 1 and VII 3 who were selected by purposive sampling technique. The research data were obtained from test questions and response questionnaires, the data were analyzed using the independent sample t-test. The results showed the average N-gain of science literacy abilities of students in the experimental class (0.48 ± 0.16) with "moderate" criteria and the control class (0.23 ± 0.13) with "low" criteria. This shows that learning using the PBL model using vee diagrams has a better effect on increasing students' scientific literacy skills. The results of the questionnaire response analysis had an average percentage was 88.8%.Keywords: Science literacy, problem based learning, vee diagram